THE EFFECT OF COMPENSATION, WORK ENVIRONMENT AND COMPANY ORGANIZATIONAL CULTURE ON EMPLOYEE JOB SATISFACTION AT HALIM FERTILITY CENTER MEDAN - Renaldi, Yori; Handoko, Bagus; Ardiani, Winda (CV. Lafadz Jaya, 2024)
This type of research is a type of Casual Associative research, the type of causal associative research (cause and effect) is a study that aims to find out whether there is a relationship between compensation variables, work environment and organizational culture on employee job satisfaction. This research was conducted in one of the companies, namely Halim Fertility Center Medan. The population in this study was 140 employees, but the sample taken was used using the Slovin formula determination with the results of 58 employee samples using the Slovin formula sampling technique. The data source used is primary data. Researchers also collect data by distributing questionnaires as many as 20 questions using Google forms. The results of this study are that the Compensation Variable (X1) partially has a negative and insignificant effect on employee job satisfaction at the Halim Fertility Center Medan. This is known from the results of the partial test (t test) which states that the value of the t-calculation coefficient> t table, 0.925> 1.67155 at a significant 0.359 <0.05. The Work Environment Variable (X2) partially has a positive and significant effect on employee job satisfaction at the Halim Fertility Center Medan. This is known from the results of the partial test (t test) which states that the value of the t-calculation coefficient> t table, 3.190> 1.67155 at a significant 0.002 <0.05. The Organizational Culture Variable (X3) partially has a positive and significant effect on employee job satisfaction at the Halim Fertility Center Medan. This is known from the results of the partial test (t-test) which states that the coefficient value of t count> t table, 2.290> 1.67155 at a significant 0.026 <0.05. Then, the results of the study also show that the Compensation Variable (X1), Work Environment (X2), and Organizational Culture (X3) simultaneously affect Employee Job Satisfaction (Y) Halim Fertility Center Medan. (coefficient value F count> F table 67.304> 2.773 at a significant 0.000 <0.05). So the previous hypothesis (H4) is accepted. The correlation is the adjusted R Square correlation figure of 0.777 in this case meaning 77.7% of employee job satisfaction can be obtained and explained by compensation, work environment, and organizational culture. While the remaining 100% - 77.7% = 22.3% is explained by other factors or variables outside the model, such as available facilities, working conditions, communication, job security, etc.